Pemaafan Dan Kemampuan Interaksi Sosial Pada Mahasiswa Program Studi Psikologi Islam Fakultas Dakwah Institut Agama Islam Negeri (IAIN) Salatiga Tahun 2018 - Ayun, Qurrotu (Konseling Edukasi : Journal of Guidance and Counseling, 2020)
Forgiveness and Social Interaction Ability of Students of the Islamic Psychology Study Program, Faculty of Da'wah, State Islamic Institute (IAIN) Salatiga 2018. This study aims to determine the extent of the relationship between the level of forgiveness and the ability of social interaction in students. Respondents in this study were 150 students of Islamic psychology study program, the Da'wah Faculty of the Islamic State Institute of Salatiga, with an age range of 17-21 years. The hypothesis proposed by the researcher is that there is a positive relationship between forgiveness variables and the ability of social interaction in students. Which means, the higher the level of forgiveness owned by students, the higher the social interaction ability. The type of data in the study is nominal and interval data. The data obtained in the study were analyzed using Karl Pearson's product moment analysis and product moment correlation which was used to see the relationship between variables. The results showed that there was a positive correlation between forgiveness and the ability of social interaction in students (r = 0.679) and p <0.01) with the contribution of forgiveness variables on social interaction ability by 46%. Another analysis used in this study is to use regression analysis to see whether there is a difference in the level of forgiveness in terms of gender, and age demographics. The results of the analysis show that there are differences in aspects of forgiveness in terms of gender and age demographics. Key Words : Forgiveness, Social Interaction, Students